KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI PECAHAN SISWA SD KELAS III MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING - Juwita, Evi Nur; Kelana, Jajang Bayu (COLLASE (Creative of Learning Students Elementary Education), 2021)
The ability to solve mathematical problems is very important in learning mathematics and needs to be developed from students at the elementary school level. This study aims to examine the scenarios and implementation of mathematics learning in the mathematical problem solving abilities of elementary school students in class III using the Snowball Throwing learning model, the response of teachers and elementary school students in grade III to mathematics learning in problem solving skills using the Snowball Throwing learning model, and the difficulties difficulties experienced by third grade elementary school students in solving mathematical problem solving problems. This research is a qualitative descriptive study with the subject of this research is the third grade students at SDIT Uswatun Hasanah Cimahi. The instruments used in the study were tests, questionnaires, interview guidelines, and observation sheets. The conclusions of this research are: 1) In carrying out mathematics learning activities in fractional material, snowball throwing learning model is very suitable to be implemented. 2) The teacher gives a very good impression of the learning carried out by the researcher. 3) The students' difficulties in this problem solving indicator are students having to think many times when taking the evaluation test.